Ambient intraborehole flow in a highly productive aquifer in Ljubljana, Slovenia - Janja Svetina; Joerg Prestor; Simon Mozetič; Mihael Brenčič (Journal of Hydrology: Regional Studies, 2025)
Study region: Ljubljansko polje aquifer in the central part of Slovenia. Study focus: Impeller flowmeter was used together with the water quality probe to determine the flow characteristics of water under ambient conditions (without pumping) in 13 boreholes in a highly productive alluvial aquifer. The study focused on analysing the characteristics and variability of intraborehole flows in relation to the technical features of the boreholes, as well as the geometry and geological composition of the aquifer. New hydrological insights for the region: The study has shown that vertical hydraulic gradients are not limited to complex multiple aquifer systems but can also occur in uniform alluvial aquifers without typical aquitard layers if hydraulic head differences exist between the upper and lower parts of the aquifer. The intraborehole flows are mainly caused by pressure-driven convection in deeper boreholes with long screens. The direction and velocity of these flows are strongly influenced by the morphology of the bedrock. Downward water flows are closely related to the local deepening of the bedrock and upward flows to the local rise of the bedrock. In some boreholes, intraborehole flow rates exceed the typical pumping rates for groundwater sampling, raising concerns about the representativeness of samples collected using conventional sampling methods. Hydrochemical logs proved to be a valuable complementary method to determine the locations of the main inflows.